Differences in fatigability of muscles involved in fecal continence: Potential clinical ramifications. Issue 24 (19th December 2021) - Patel, Krupa; Mei, Ling; Yu, Elliot; Kern, Mark; Lehal, Navjit; Edeani, Francis; Sanvanson, Patrick; Davidson, Emily R. W.; Shaker, Reza
Abstract: Introduction: Fatigue of the anal sphincter complex has been demonstrated using high‐resolution anorectal manometry (HRAM). However, the fatigability of individual muscles such as the external anal sphincter (EAS) and puborectalis muscles (PRM) has not been described. Vaginal manometry has been used to study contractile activity of the PRM. By applying both modalities, we attempted to differentiate the fatigability between the PRM and the EAS under different exercise conditions. Methods: We studied two groups: group 1, 12 healthy women (21 ± 2.7 years) with HRAM and group 2, 10 healthy (20 ± 3 years) women with vaginal manometry. All subjects performed 40 repetitive contractions with and without an intra‐anal resistive load. In group 1, areas under the curve (AUC) of the anal canal high‐pressure zone (HPZ) including the caudal and rostral halves were compared. In group 2, the maximum and mean pressures of the vaginal HPZ were compared. Results: The AUC decreased significantly only after repetitive contractions against a resistive load (462 ± 129 vs. 390 ± 131 mmHg‐cm, p = 0.02), indicating fatigue. The caudal half (EAS) decreased significantly after contractions against a load (288 ± 75 vs. 239 ± 82 mmHg‐cm, p = 0.02), while the rostral half (PRM) did not. The vaginal pressures (PRM) also decreased only after repetitive contractions against a load (maximum pressures, 358 ± 171 vs. 239 ± 109 mmHg, p = 0.02). Conclusions: The EAS and PRM both exhibit fatigue with contractions only against a resistive load. These findings may guide the development of appropriate exercise regimens to target specific muscles involved in fecal continence. Abstract : Fecal incontinence is a prevalent and distressing disorder with a mainstay of treatment being pelvic floor muscle exercises. Fatigue is a principle of strengthening exercises. Individual continence muscles have not been studied until this study showing the fatigability of both the external anal sphincter and puborectalis muscles.